A Nimble Arc : James Van Der Zee and Photography - Boone, Emilie (Book collections on Project MUSE., 2023)
"In A Nimble Arc Emilie Boone considers James Van Der Zee's photographic work across the twentieth century-from his early years in Harlem to the moment of the Harlem on my Mind exhibit-to foreground aspects of Black quotidian life. Boone theorizes 'nimble' to describe the ease of movement with which one must transition between art history and vernacular photography when considering Van Der Zee and his work. While Van Der Zee is lauded for his role in the Harlem Renaissance and his late-career portrait of Jean-Michel Basquiat, his studio played a major role in the Black community for decades, photographing ordinary people and events in ways that have been mostly overlooked. Boone's account recasts our understanding not only of this canonical figure, but of photography in Black life more generally"--